A STUDY OF OBSTETRIC HYSTERECTOMY OVER A PERIOD OF 5 YEARS AT CUSMCH - RAHUL M RATHOD; HARSHDEEP K JADEJA; BHAVESH B AIRAO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study aimed (1) to determine the indication of obstetric hysterectomy and (2) to determine the fetomaternal outcome. Methods: This is a hospital-based retrospective study carried out in the Department of Obstetrics and Gynecology, C.U.Shah Medical College and Hospital from January 2018 to December 2020. Results: Out of 8881 deliveries during our study period, there were a total of 20 patients who underwent an obstetric hysterectomy, the incidence being 0.2%. Nine cases out of 6871 vaginal deliveries and 11 cases out of 2510 cesarean deliveries required an obstetric hysterectomy. Maximum patients, seven out of 20 were between 31 and 35 years age group followed by six patients between 36 and 40 years and five patients above 41 years. Only two patients were below 30 years of age. Most of the cases (70%) belonged to the lower middle class and 30% were from the upper middle class. About 60% were registered antenatal care (ANC) cases while 40% never visited any health-care facility. Out of 20 patients who underwent an obstetric hysterectomy, 18 patients (90%) were referred from another center while only 2 patients (10%) were admitted at our center. Eleven patients that are 55% delivered outside the institute among which three patients were home delivered by unskilled birth attendants. Nine patients were delivered at our center and among these sseven patients were referred from adjoining primary health-care centers, community health-care centers, and other private hospitals. Our institute being a tertiary hospital, maximum high-risk and complicated deliveries were referred. Conclusion: Obstetric hysterectomy is an unwanted but necessary emergency in obstetrics. It is a life-saving procedure in many catastrophic conditions, although it curtails the future. Good ANC, identification of risk factors, timely referral, and intervention at a well-equipped hospital can reduce obstetric hysterectomies. With the increasing incidence of cesarean deliveries and morbidly adherent placenta, the need for obstetric hysterectomy is increasing. With the improvement of modern obstetrics and modern modalities for the treatment of postpartum hemorrhage and adherent placenta, there is a reduction in the number of obstetric hysterectomies.